2005
DOI: 10.1091/mbc.e04-04-0277
|View full text |Cite
|
Sign up to set email alerts
|

R-Ras Controls Membrane Protrusion and Cell Migration through the Spatial Regulation of Rac and Rho

Abstract: Although it is known that the spatial coordination of Rac and Rho activity is essential for cell migration, the molecular mechanisms regulating these GTPases during migration are unknown. We found that the expression of constitutively activated R-Ras (38V) blocked membrane protrusion and random migration. In contrast, expression of dominant negative R-Ras (41A) enhanced migrational persistence and membrane protrusion. Endogenous R-Ras is necessary for cell migration, as cells that were transfected with siRNA f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 69 publications
11
89
2
Order By: Relevance
“…3B). Consistent with the implication that compromised cell motility and invasiveness in myr-Akt1-expressing cells was due to inhibition of Rho activity, treatment with exoenzyme C3 transferase (C3 toxin), which inhibits Rho when added to the media (45,46), was as effective at blocking cell migration as was expression of myrAkt1 (Fig. 3C).…”
Section: Cell Spreading and Formation Of Focal Adhesions Are Inhibitesupporting
confidence: 73%
“…3B). Consistent with the implication that compromised cell motility and invasiveness in myr-Akt1-expressing cells was due to inhibition of Rho activity, treatment with exoenzyme C3 transferase (C3 toxin), which inhibits Rho when added to the media (45,46), was as effective at blocking cell migration as was expression of myrAkt1 (Fig. 3C).…”
Section: Cell Spreading and Formation Of Focal Adhesions Are Inhibitesupporting
confidence: 73%
“…7 Notably, two conserved arginine residues are essential for R-Ras inactivation by plexins, and their point mutation results in the loss of most (although not all) functional responses mediated by plexins. 68,73,91 R-Ras is a major positive regulator of integrin function: 92 it gets activated upon cell contact to the ECM, 93 and in turn it sustains the clustering and activation of β1-integrin receptors (as well as others), it enhances focal adhesion formation and cell adhesion, and it regulates positively cell spreading, cell migration and invasion, as well as axon outgrowth (for a general review see ref. functions qualify R-Ras as the ideal target for the inhibitory activity of semaphorins; nonetheless the molecular mechanisms involved in this pathway are presently unclear.…”
Section: Integrins and The Actin Cytoskeleton Are Major Targets Of Plmentioning
confidence: 99%
“…However, two recent reports demonstrated that R-Ras signaling instead induces RhoA activation and Rac1 inactivation at the leading edge, via still unknown pathways. 93,97 Therefore, further studies are required to elucidate the mechanism whereby R-Ras inactivation mediated by semaphorins may regulate cell adhesion and cell migration.…”
Section: Integrins and The Actin Cytoskeleton Are Major Targets Of Plmentioning
confidence: 99%
“…In 2002, Evellin et al (76) demonstrated that PLC-ε appeared to be stimulated by GPCRs through the formation of cAMP and activation of Rap2B. Rap2B may promote cell adhesion, spread, migration and polarity, in addition to integrin activation, axonal outgrowth and phagocytosis, through interacting with R-Ras effectors such as PLC-ε (76)(77)(78)(79)(80)(81)(82)(83).…”
Section: Rap2b Interacts With Phospholipase C (Plc)-ε and Activates Itmentioning
confidence: 99%